Early Child Neglect: Does It Predict Obesity or Underweight in Later Childhood? - Bennett, David S. (2010)
Child neglect has been hypothesized to be a risk factor for both obesity and underweight in early childhood, although little research has examined the relation between neglect and body mass index (BMI). The current study examined the relation between neglect and BMI among 185 children (91 with a Child Protective Services [CPS] history of neglect) who were initially seen at ages 4–6 years and who were followed through ages 7–9 years. Neglected and comparison children were found to have similar BMIs, although both groups had BMIs that were significantly greater than Centers for Disease Control and Prevention (CDC) norms for age, gender, and ethnicity. Neglect chronicity did predict lower BMIs but only at ages 8 and 9 years. The current findings suggest that greater examination of moderators is needed to identify the specific contexts in which neglect is related to children’s weight.